IMPLEMENTATION OF THE NETWORK STATION SYSTEM ON TVRI BALI - Muliarta, I Nengah (Seni Media Rekam ISI Surakarta, 2020)
The democratization of broadcasting in Indonesia is manifested in the implementation of the Network Station System (Sistem Stasiun Jaringan / SSJ) by striving for diversity of ownership and broadcast content in broadcasting institutions. SSJ is also an effort to decentralize broadcasting so that people in the regions get information related to their own regions through subsidiary networks or local broadcasting institutions. TVRI is the only public broadcasting institution that has network subsidiaries throughout Indonesia. This research uses a case study approach, an approach to intensively examine a case with a focus on TVRI Bali. Data collection used interview and observation methods. Data analysis using the Interactive Analysis approach. The results showed that TVRI Bali has not been able to fully implement SSJ. TVRI Bali can only meet the provisions of local broadcast content with a percentage of up to 20%, but has not been able to fulfill the spirit of diversity of ownership according to the basic concept of SSJ. In addition, the principle of diversity of ownership has not been fulfilled due to inconsistencies between the Broadcasting Law and Government Regulation Number 13/2005 and Ministerial Regulation 43/2009 which specifically regulates private television broadcasting institutions.